Phenotypes of gene disruptants in relation to a putative mitochondrial malate–citrate shuttle protein in citric acid-producing Aspergillus niger. Issue 9 (1st September 2016) - Kirimura, Kohtaro; Kobayashi, Keiichi; Ueda, Yuka; Hattori, Takasumi
Abstract: The mitochondrial citrate transport protein (CTP) functions as a malate–citrate shuttle catalyzing the exchange of citrate plus a proton for malate between mitochondria and cytosol across the inner mitochondrial membrane in higher eukaryotic organisms. In this study, for functional analysis, we cloned the gene encoding putative CTP ( ctpA ) of citric acid-producing Aspergillus niger WU-2223L. The gene ctpA encodes a polypeptide consisting 296 amino acids conserved active residues required for citrate transport function. Only in early-log phase, the ctpA disruptant DCTPA-1 showed growth delay, and the amount of citric acid produced by strain DCTPA-1 was smaller than that by parental strain WU-2223L. These results indicate that the CTPA affects growth and thereby citric acid metabolism of A. niger changes, especially in early-log phase, but not citric acid-producing period. This is the first report showing that disruption of ctpA causes changes of phenotypes in relation to citric acid production in A. niger . Graphical abstract: : Disruption of the gene encoding the citrate transport protein (CTPA, i.e., malate–citrate shuttle protein) affects the phenotype of Aspergillus niger .